Improvement of skin condition in striae distensae: development, characterization and clinical efficacy of a cosmetic product containing Punica granatum seed oil and Croton lechleri resin extract - Bogdan C; Iurian S; Tomuta I; Moldovan M (Dove Medical Press, 2017)
Cătălina Bogdan,1 Sonia Iurian,2 Ioan Tomuta,2 Mirela Moldovan1 1Department of Dermatopharmacy and Cosmetics, 2Department of Pharmaceutical Technology and Biopharmacy, Faculty of Pharmacy, University of Medicine and Pharmacy Iuliu Hatieganu, Cluj-Napoca, Romania Abstract: Striae distensae are a frequent skin condition associated with pregnancy, weight change or lack of skin elasticity. The aim of this research was to obtain a topical product containing herbal active ingredients with documented antioxidant and anti-inflammatory activity (Punica granatum seed oil and Croton lechleri resin extract) and demonstrate its positive effect on prevention and treatment of striae distensae. First, the cream base formulation was optimized through experimental design. Secondly, the cream containing the two active ingredients was investigated in an interventional nonrandomized clinical trial. The clinical outcome was assessed through biophysical parameters and ultrasonographic evaluation. The state of the skin was evaluated by biophysical measurements and ultrasonography at the beginning of the study and after 3 and 6 weeks. The experimental design was successfully used to set the best ranges for the technological and formulation factors to obtain a cosmetic formulation with optimal characteristics. The study of clinical efficacy on the optimal formulation revealed an increase in the dermis thickness, hydration and elasticity values in both groups after 6 weeks of cream application. The new oil-in-water cream containing P. granatum seed oil and C. lechleri resin extract can be helpful in the prevention or improving of skin changes associated with striae. Keywords: stretch marks, ultrasonography, texture analysis, design of experiments, oil-in-water emulsion